Sleep Health as Measured by RU SATED: A Psychometric Evaluation. Issue 1 (2nd January 2021) - Ravyts, Scott G.; Dzierzewski, Joseph M.; Perez, Elliottnell; Donovan, Emily K.; Dautovich, Natalie D.
ABSTRACT: Objective/Background : Sleep health is a multidimensional construct of sleep and wakefulness that operationalizes optimal sleep as more than the absence disease. Despite its importance to public health promotion efforts, empirical research examining sleep health is currently limited, possibly due to the lack of empirically validated measures. Therefore, the purpose of the current study was to evaluate the psychometric properties of a previously proposed six-item sleep health scale (RU- SATED). Participants : A sample of 3, 401 adults (Mean Age = 42.77, 47.8% female) completed an online survey of sleep and health. Methods : Participants completed the RU-SATED scale, as well as other sleep-related measures including the Insomnia Severity Index (ISI) and the Sleep Self-Efficacy Scale (SSE). Results : An exploratory factor analysis (EFA) revealed a two-factor structure. A confirmatory factor analysis (CFA) using this two-factor structure demonstrated adequate to good model fit indices ( X 2 = 45.96, df = 8, p < .01; RMSEA = .04; CFI = .98; NFI = .98; TLI = .97). Cronbach's α was .64 and the average interitem correlation was .22. RU-SATED was negatively associated with insomnia severity and positively associated with both self-reported sleep and sleep self-efficacy. Conclusions : RU-SATED appears to be a valid instrument for the assessment of sleep health among adults that is related to, but distinct from, other established sleep constructs. Future research may benefit from examining the test–retest reliability of the measure and assessing the predictive validity of sleep health as it relates to health-related outcomes.